Indigenous Tribes in the Brazilian Amazon: Finding a Balance between Sustainability and Economic Development - O'Donnell, Bernadette R (2018)
The number of isolated indigenous tribes in Brazil is dropping due to a multitude of factors, including resource extraction. If these factors continue, there will be further reduction of the population of indigenous tribes which causes the loss of culture of the world’s oldest societies. This research establishes the roles that the Brazilian government, NGOs, and the international community should play to preserve indigenous tribes. The research question is: How can Brazil sustain isolated indigenous tribes in the Amazon without compromising its own economic development? The research method is the modified Delphi method which results in a consensus of experts on the best practices to sustain these tribes. This study’s findings show that combining a new Brazilian economic model, decreasing climate change, creating and enforcing land demarcations, increasing indigenous involvement, and advocacy, and adding pressure from the international community can reverse the decline of the isolated indigenous population in the Brazilian Amazon, preserving any remaining culture and identity for these communities